KAJIAN BAHAN KOLEKTOR YANG BERBEDA TERHADAP KELIMPAHAN DAN PERTUMBUHAN KERANG HIJAU (Perna viridis) DI PERAIRAN PESISIR - Astuti, Dwi Anggun; Sutaman; Mulatsih, Sri (Journal Sains dan Teknologi Budidaya Perairan (SINTASAN), 2023)
Green mussel (Perna viridis) is one of the biological resources that have high economic value in Indonesia. This green mussel thrive in the gulf waters, the waters around mangroves area, and estuaries, with a muddy and sandy waters in the environment condition, with light and moving water, and salt levels are not too high. This is because of the green mussel is easy and relatively fast incultivation.Based on the results of the study, concluded that the physical parameters of water chemistry there is no difference between treatments real and viable for aquaculture activities for collectors of differentmaterials on the abundance and growth of green mussel (Pernaviridis). C treatment is the best treatment(net material) during the study and very significant effect on daily growth rate (gram) F count = 12,0222> F table 0.05 (18:56) = 2.03, growth of absolute weight biomass (Gram) F count = 3.0381> F table0.05 (18:56) = 2.03 daily growth (%) F count = 15.4305> F table 0, 05 (18:56) = 2, 03, the relativegrowth (g) F count = 3.7151> F table 0.05 (2: 6) = 2.03, and no significant effect on diameter (cm) Fcount = 0.0417> F table 0.05 (18:56) = 2.03, and density (cm) F count = 0.0180> F table 0.05 (18:56)= 2.03.